Before It Gets Better: The Short-Term Employment Costs of Regulatory Reforms - Andrea Bassanini; Federico Cingano (Institute of Labor Economics (IZA), 2017)
We exploit long time series of industry-level data in a group of OECD countries to analyze the short-term labor market effects of reforms lowering barriers to entry and dismissal costs. Our estimates show that both policies induce non-negligible transitory employment losses, a result that is confirmed by complementary evidence from case studies of three recently implemented EPL reforms. The strength of these effects varies depending on the underlying industry and labor market structure, and on cyclical conditions: the employment cost of deregulation is higher in economic downturns, negligible in good times. These findings prove robust to a set of specification and sensitivity checks, and are confirmed after standard reverse causality and falsification tests.
Keywords: J23; L51; L11; 330; product market regulation; EPL; employment losses; industry data